Theory and research on human emotions - Turner, Jonathan H. (Advances in group processes ;, 2004)
The sociology of emotions is now at the forefront of micro social theory and research; and increasingly, the dynamics of emotions are seen as one of the ways to link micro to macro-level social processes. For in the end, what drives people to create social structures and to maintain commitments to these structures is emotion. The papers in this volume represent a broad array of approaches to the analysis of emotions. Some come from well established traditions in social psychology and micro sociology traditions such as symbolic interactionism, expectation states research, interaction ritual theory, and power-status theory. Others come from more macro-oriented theorizing in Europe; another set comes from meso-level analysis of organizational structures; and still others come from the opposite end of the intellectual continuum and explore the physiology and evolution of emotions. The goal of the volume is to sample the range of work in an area that did not exist three decades ago in sociology and to see the theoretical and research programs that sociological theorists and researchers on emotions are pursuing. The sociology of emotions is now a broad-based intellectual movement, with the result that no one volume can fully capture the diversity of work being performed by sociologists. Still, this volume attempts to provide readers with a review of some of the more creative work on emotional dynamics in human groupings.